2008
DOI: 10.1007/s11999-008-0373-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric PCL Insufficiency from Tibial Insertion Osteochondral Avulsions

Abstract: Posterior cruciate ligament (PCL) insertion-site osteochondral avulsions in children, particularly from the tibia, are not commonly seen by orthopaedic surgeons. Because of the rarity of these injuries, careful attention to the specific physical examination and imaging findings seen with these injuries is necessary so that the proper diagnosis can be made. Osteochondral avulsions of the PCL can be missed on plain radiographs in skeletally immature patients, and therefore magnetic resonance imaging is necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
(49 reference statements)
4
24
0
Order By: Relevance
“…Although this finding concurred with previous reports of bony avulsions at the tibial attachment of the PCL, 20,24,25,34 our study might reveal agedependent failure patterns in the tibia attachment of the PCL. Some authors have suggested the mechanism of PCL injuries in children as follows: hyperflexion injury often caused by a fall with the ankle in plantar flexion and a direct blow to the anterior tibia, which results in a PCL avulsion, usually with bone or perichondral femoral fragment.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although this finding concurred with previous reports of bony avulsions at the tibial attachment of the PCL, 20,24,25,34 our study might reveal agedependent failure patterns in the tibia attachment of the PCL. Some authors have suggested the mechanism of PCL injuries in children as follows: hyperflexion injury often caused by a fall with the ankle in plantar flexion and a direct blow to the anterior tibia, which results in a PCL avulsion, usually with bone or perichondral femoral fragment.…”
Section: Discussionsupporting
confidence: 93%
“…32 Tibial avulsion of the PCL, which is seldom seen in the literature, results from a direct blow to the proximal tibia with the knee flexed. 20,25,26,34 In our study, falls resulted in force to the proximal tibia in 5 of the 6 patients, corresponding with earlier studies. 20,25,26,34 Plain radiographs often underestimate the size of the largely cartilaginous fragment or are negative.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Radiographs may also show an avulsion fracture. Management is generally conservative, with consideration of acute repair being reserved for the elite athlete with severe laxity [55].…”
Section: Cruciate Ligament Injuriesmentioning
confidence: 99%